Spatial augmented reality for product appearance design evaluation. Issue 1 (6th December 2014) - Park, Min Ki; Lim, Kyu Je; Seo, Myoung Kook; Jung, Soon Jong; Lee, Kwan H.
Abstract: Augmented reality based on projection, called "Spatial Augmented Reality (SAR)", is a new technology that can produce immersive contents by overlapping virtuality and real-world environment. It has been paid attention as the next generation digital contents in media art and human–computer interaction (HCI). In this paper, we present a new methodology to evaluate the product appearance design more intuitively by means of SAR technique. The proposed method first projects the high-quality rendered image considering the optical property of materials onto the mock-up of a product. We also conduct a projector-camera calibration to compensate a color distortion according to a projector, a projection surface and environment lighting. The design evaluation methodology we propose offers more flexible and intuitive evaluation environment to a designer and user (evaluator) than previous methods that are performed via a digital display. At the end of this research, we have conducted a case study for designing and evaluating appearance design of an automobile.